1931
DOI: 10.1139/cjr31-050
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effect of Monochromatic Light Upon Plasmolysis in Paramecium

Abstract: Investigations conducted during the last three years have shown that light of definite wave-lengths has specific effects upon the growth of organisms, e.g., yeast, paramecium and tomato rot (Colletotrichum).The organism, Paramecium caudatum, was irradiated in a quartz cell at room temperature with a Cooper-Hewitt "Lab-arc" for periods of 6 and 24 hr. and the rate of plasmolysis in sodium chloride and sucrose solutions then determined. The organisms passed through the same series of reactions in both solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1956
1956
1970
1970

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Permeability increased as the duration to light was prolonged and this factor had a bearing on growth, especially in pure cultures which contained diffusible substances in, the medium. Hutchison andAshton (1929, 1931) reported that when P. caudatum was irradiated with monochromatic light certain frequencies in the red, yellow, and the near ultraviolet were found to stimulate growth.…”
Section: Discussionmentioning
confidence: 99%
“…Permeability increased as the duration to light was prolonged and this factor had a bearing on growth, especially in pure cultures which contained diffusible substances in, the medium. Hutchison andAshton (1929, 1931) reported that when P. caudatum was irradiated with monochromatic light certain frequencies in the red, yellow, and the near ultraviolet were found to stimulate growth.…”
Section: Discussionmentioning
confidence: 99%
“…Light affected the amoebae either through absorption by intracellular pigment(s) or through binding to the amoebae of a photosensitizing compound in the medium. Among protozoa, photoinhibition of growth has been shown in cultures ofParamecium (9,20), Tetrahymena (7,16), Blepharisma (8), and in bleached phytoflagellates (3). The response of sarcodinid cultures to light has not been reported except for some observations of phototaxis and cytokinesis by Prescott (18) and by my preliminary reports (4,5).…”
mentioning
confidence: 99%